2020
DOI: 10.4314/njtd.v17i3.9
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Intensity Analysis for Synoptic Stations in Northern Nigeria

Abstract: With the large inter-annual variability of rainfall in Northern Nigeria, a zone subject to frequent dry spells which often result in severe and widespread droughts, the need for intense study of rainfall and accurate forecast of rainfall intensity duration frequency (IDF) curves cannot be over emphasized. The Intensity Duration Frequency relationship is a mathematical relationship between the rainfall intensity and rainfall duration for given return periods. Using a subset of the network of fifteen continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Statistical tools were engaged to determine the seasonal spatial variations of the retrieved climate data. Oyegoke et al [13] indicated that statistical techniques of analysis are essential normally to precisely evaluate rainfall data for effective planning and for future forecasts regarding proficient and operative water resources management. The coefficient of variation (CV) was used to examine the extent of rainfall variation.…”
Section: Rainfall and Temperature Datamentioning
confidence: 99%
“…Statistical tools were engaged to determine the seasonal spatial variations of the retrieved climate data. Oyegoke et al [13] indicated that statistical techniques of analysis are essential normally to precisely evaluate rainfall data for effective planning and for future forecasts regarding proficient and operative water resources management. The coefficient of variation (CV) was used to examine the extent of rainfall variation.…”
Section: Rainfall and Temperature Datamentioning
confidence: 99%
“…The rainfall-runoff processes can be simulated by several powerful models that synthesize distinct components (Adnan and Atkinson, 2012;Awadalla and Noor, 1991), such as evapotranspiration, infiltration, detention or depression storage, overland flow and finally stream flow. The slope and timing of the hydrograph from a given storm event, in a catchment, is a function of several physiographic factors, such as rainfall intensity and duration, size, slope, shape, storage and morphology of watershed, land use, and cover, soil type and imperviousness (McCuen, 1989;Basarudin et al, 2014;Oyegoke et al 2020). These factors influence streamflow in a basin.…”
Section: Introductionmentioning
confidence: 99%
“…There is a compelling need for updating and reassessment of the IDF curves and equations on regular basis. A review of previous IDF studies at Oleh and it environ include Metibaye et al [2], Ologhadien and Nwaogazie [3], Oyegoke et al [4] and Nwaogazie et al [5]). The review shows that IDF curves/equation for Oleh municipality are not available and consequently will be developed.…”
Section: Introductionmentioning
confidence: 99%